If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13n + -2 + -1n + 5 = 0 Reorder the terms: -2 + 5 + 13n + -1n = 0 Combine like terms: -2 + 5 = 3 3 + 13n + -1n = 0 Combine like terms: 13n + -1n = 12n 3 + 12n = 0 Solving 3 + 12n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 12n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 12n = 0 + -3 12n = 0 + -3 Combine like terms: 0 + -3 = -3 12n = -3 Divide each side by '12'. n = -0.25 Simplifying n = -0.25
| 3/8+2/9-1/4 | | 12w^2+19w=4 | | 1.4c-0.66c+0.74c=0 | | 4(2+4y)=16y+10 | | 5x-15=4x | | 18x+9=3(6x+3) | | 18x+9=3(6x+3) | | 5/9x12/25 | | X-4/3 | | 30*-30= | | x+8y=6 | | 5/6-7/8 | | c=k+273.15 | | 3v+8+5v=-4(6+v)+2(4+3v) | | 2/1.2=5/k | | 2*r^2= | | -7(-7-r)=-5r-23 | | 60=5(3-3m) | | x*.2=39 | | 36/24=16/z | | m+(2m+4)=94 | | x*.2=45 | | x*.02=45 | | 3x^2+4=31 | | x/63=4/9 | | 72-4x= | | s-7=-3-6(4x-6) | | 1+4k=-3k+8 | | -14+8a=8a-8-2a | | 4h(5+3)=5h(6-2) | | n-8-6n=12 | | 3(h-7)=-22+4b |